Effects of sex, educational background, and chronic kidney disease grading on longitudinal cognitive and functional decline in patients in the Japanese Alzheimer's Disease Neuroimaging Initiative study. Issue 1 (12th July 2018) - Iwata, Atsushi; Iwatsubo, Takeshi; Ihara, Ryoko; Suzuki, Kazushi; Matsuyama, Yutaka; Tomita, Naoki; Arai, Hiroyuki; Ishii, Kenji; Senda, Michio; Ito, Kengo; Ikeuchi, Takeshi; Kuwano, Ryozo; et al.
Abstract: Introduction: The objective of this study was to determine whether sex or education level affects the longitudinal rate of cognitive decline in Japanese patients in the Alzheimer's disease Neuroimaging Initiative study with defined mild cognitive impairment (MCI). Methods: We accessed the entire Japanese Alzheimer's Disease Neuroimaging Initiative data set of 537 individuals, among whom 234 had MCI and 149 had Alzheimer's disease. We classified participants into three categories of educational history: (1) low, 0 to 9 years; (2) moderate, 10 to 15 years; and (3) high ≥16 years. We examined the main effects and interactions of visit, sex, and educational achievement on scores for the Clinical Dementia Rating Sum of Boxes, Alzheimer's Disease Assessment Scale–cognitive subscale 13, Mini‐Mental State Examination, and Functional Activities Questionnaire in a longitudinal manner. Results: Women with MCI had a significantly faster rate of decline than men over a 3‐year period. Highly educated men showed a significantly slower rate of decline than the other groups. Sex differences in the rates of decline remained after stratification by amyloid or apolipoprotein E ( APOE ) ε4 status but were absent in Alzheimer's disease over a 2‐year period. Subtle differences in chronic kidney disease grade affected the rate of decline. A higher Fazekas periventricular hyperintensity score was associated with a lower estimated glomerular filtration rate in women only. Discussion: In patients with MCI, sex and educational history significantly affected the rate of change in cognitive and clinical assessments. Furthermore, a subtle decline in chronic kidney disease grade was associated with a faster rate of decline regardless of amyloid pathology in women.